Entrepreneurial Orientation and Knowledge Transfer: analysis in Spanish family businesses - Ascensión Barroso-Martínez; Ramón Sanguino-Galván; Tomas Manuel Bañegil-Palacios (Tourism & Management Studies, 2016)
This study tries to answer the following research questions in the context of family-owned firms: How is knowledge management related to entrepreneurship? How are knowledge management and entrepreneurship related to business performance? How does the family influence the above relationships? To answer these questions we performed a study to firms belonging to Family Business Regional Associations. The methodology used to analyze these relationships is based on a structural equation approach (SEM), specifically Partial Least Squares (PLS). The main value of this study is the proposition of two models. The first model analyzes the relationship among Knowledge Transfer (KT), Entrepreneurial Orientation (EO) and Performance (PERF). The second model studies the Family Influence (FI) as a moderating variable of such relationships. As conclusion, in these family firms KT has a significant positive effect on EO, and the latter on PERF. FI strengthening moderates the relationship between KT and EO and PERF. The implications for managers are clear. Our study provides a theoretical and empirical basis for further study on KT and EO in family business.